2021
DOI: 10.3389/fcell.2020.584220
|View full text |Cite
|
Sign up to set email alerts
|

C-Terminal Binding Proteins Promote Neurogenesis and Oligodendrogenesis in the Subventricular Zone

Abstract: C-terminal binding proteins (CtBPs) are transcriptional modulators that can regulate gene expression through the recruitment of a corepressor complex composed of chromatin-modifying enzymes and transcriptional factors. In the brain, CtBPs have been described as regulators of cell proliferation, differentiation, and survival. Nevertheless, the role of CtBPs on postnatal neural stem cells (NSCs) fate is not known yet. Herein, we evaluate the expression and functions of CtBPs in postnatal NSCs from the subventric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…So far, MTOB was used in brain cells mainly at high concentrations (1-5 mM), leading to apoptosis [17,23]. In a previous report, we showed that low levels of MTOB (up 100 µM) were not toxic to neural stem cell cultures and promoted neuronal differentiation and maturation, and oligodendrogenesis [17], suggesting that CtBP may co-activate genes beneficial for brain regeneration. Herein, we observed a toxic effect of MTOB per se at high concentrations, namely at 1000 µM and 2500 µM.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…So far, MTOB was used in brain cells mainly at high concentrations (1-5 mM), leading to apoptosis [17,23]. In a previous report, we showed that low levels of MTOB (up 100 µM) were not toxic to neural stem cell cultures and promoted neuronal differentiation and maturation, and oligodendrogenesis [17], suggesting that CtBP may co-activate genes beneficial for brain regeneration. Herein, we observed a toxic effect of MTOB per se at high concentrations, namely at 1000 µM and 2500 µM.…”
Section: Discussionmentioning
confidence: 84%
“…Interestingly, a missense mutation on CtBP1 was found in patients presenting neurodevelopmental deficits (e.g., ataxia, intellectual disability), further supporting the role of CtBP in central nervous system development [16]. Recently, we have demonstrated that CtBP are expressed in subventricular zone neural stem/progenitor cells, and the exposure of neonatal neural stem cell cultures to an unspecific ligand of CtBP, the 4-methylthio 2-oxobutyric acid (MTOB), resulted in enhanced neurogenesis and neuronal complexity as well as increased oligodendrogenesis indicating their potential for regenerative therapies [17].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation